Mycobacterium smegmatis Vaccine Vector Elicits CD4+ Th17 and CD8+ Tc17 T Cells With Therapeutic Potential to Infections With Mycobacterium avium - Kannan, Nisha; Haug, Markus; Steigedal, Magnus; Flo, Trude Helen (Frontiers in Immunology, 2020)
Mycobacterium avium (Mav) complex is increasingly reported to cause non-tuberculous infections in individuals with a compromised immune system. Treatment is complicated and no vaccines are available. Previous studies have shown some potential of using genetically modified Mycobacterium smegmatis (Msm) as a vaccine vector to tuberculosis since it is non-pathogenic and thus would be tolerated by immunocompromised individuals. In this study we used a mutant strain of Msm disrupted in EspG3, a component of the ESX-3 secretion system. Infection of macrophages and dendritic cells with Msm espG3 showed increased antigen presentation compared to cells infected with wild-type Msm. Vaccination of mice with Msm espG3, expressing the Mav antigen MPT64, provided equal protection against Mav infection as the tuberculosis vaccine, Mycobacterium bovis BCG. However, upon challenge with Mav, we observed a high frequency of IL-17 producing CD4+ (Th17 cells) and CD8+ (Tc17 cells) T cells in mice vaccinated with Msm espG3::mpt64 that was not seen in BCG-vaccinated mice. Adoptive transfer of cells from Msm espG3 vaccinated mice showed that cells from the T cell compartment contributed to protection from Mav infection. Further experiments revealed Tc17-enriched T cells did not provide prophylactic protection against subsequent Mav infection, but a therapeutic effect was observed when Tc17-enriched cells were transferred to mice already infected with Mav. These initial findings are important, as they suggest a previously unknown role of Tc17 cells in mycobacterial infections. Taken together, Msm espG3 shows promise as a vaccine vector against Mav and possibly other (myco)bacterial infections.